FUNDAMENTALS OF STATE REGULATION OF SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP - Shamsieva Feruza Muratkhodjaevna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article presents ideas and comments on the study of the theoretical and methodological foundations of the organizational and economic mechanism of the activities of small businesses and business entities, the assessment of the place of the foundations of state regulation of small businesses and private entrepreneurship, the study of the importance of small businesses in the development of the country’s economy, the economic analysis of the activities of small businesses in the Namangan region, the development of measures to increase the export potential of the Namangan region through the regulation of small businesses and private entrepreneurship.